PENDAMPINGAN PENCEGAHAN KANKER PAYUDARA MELALUI PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA - Riski Akbarani; Faiza , Eva Inayatul; Alfia Hildayanti, Rezha (Universitas Kadiri, 2024)
Breast cancer is a health problem experienced by women throughout the world. This incident can occur at puberty, but is more common at older ages. Early detection is a very important first step to find out early the presence of a tumor or lump in the breast so that it can reduce the death rate due to cancer. The earlier breast cancer is found, the easier it will be to treat it. The aim of this activity is to increase the knowledge of young women about breast self-examination to detect breast cancer early. The method used in the initial stage was a survey, the second stage was lecture and practice, and the third stage was evaluation. The result is an increase in knowledge about breast self-examination, but there is still a need for socialization and motivation about the importance of regular breast self-examination for early detection of breast cancer.